Risk preference based option pricing in a fractional Brownian market - Stefan Rostek; Rainer Schöbel (Eberhard Karls Universität Tübingen, Wirtschaftswissenschaftliche Fakultät, 2006)
We focus on a preference based approach when pricing options in a market driven by fractional Brownian motion. Within this framework we derive formulae for fractional European options using the traditional idea of conditional expectation. The obtained formulae - as well as further results - accord with classical Brownian theory and con?rm economic intuition towards fractional Brownian motion. Furthermore the in?uence of the Hurst parameter H on the price of a European option will be analyzed.
urn:nbn:de:bsz:21-opus-21835
Keywords: G13; 330; Fractional Brownian motion; Conditional expectation; Risk preference based option pricing; Fractional option pricing; Fractional Greeks; Optionspreistheorie; Risikopräferenz; Stochastischer Prozess; Theorie